Socio-economic development for happier households: The residents’ perspectives/ Vloreen Nity Mathew - Mathew, Vloreen Nity; Voon, Boo Ho; Goh, Kelvin, T.H.; Abang Azlan, Muhammad; Phang, Grace, I. (Universiti Teknologi MARA, Perak, 2022)
The government plays a very important role in providing for its people in terms of developing opportunities to improve the household’s socio-economic development. But how far has the local government developments made the people happy? Finding a balance between the socio-economic development and the happiness of the household concern is important to sustain the development well. This paper discusses the government initiatives and perspectives from the residents of Batu Kawa on household happiness are also reported. Data were analysed using pictography and focus group discussions. The findings show that the local government is responsible for doing their part quite well in providing the basic needs of the residents, though some improvements and addition to amenities would be essential to contribute to happiness among the households in the studied area.